Peran Penegak Hukum Satresnarkoba Polresta Magelang Dalam Kasus Residivis Pelaku Kejahatan Narkoba - Martin, Lydyana Trisnaeni; Neva Tri Saharany; Jihan Rupa Puspa Ayu; Dimas Herdian Nugrahimsyah; Agung Widya Setya Pratama; Ania Nasyira; Indira Swasti Gama Bhakti (Pusat Riset dan Inovasi Nasional, 2025)
Magelang Regency, located in Central Java Province, is facing serious problems related to drug abuse. Drugs are an abbreviation of narcotics, psychotropics, and other dangerous addictive substances. In the law enforcement strategy, the Drug Investigation Unit has implemented a law enforcement strategy including investigations and inquiries, this is conducting in-depth investigations of drug networks and perpetrators of abuse. This study uses a normative and empirical approach. The data sources consist of primary and secondary data. There has been an unlawful act which is contained in Article 112 paragraph (1) of Law Number 35 of 2009 concerning Narcotics, which occurred on the side of the road into the Salaman District area, Magelang Regency on Monday, January 6, 2025 at around 22.30 WIB. The results of the study concluded that the Drug Investigation Unit of the Magelang Police played a crucial role in handling recidivists in drug cases through prevention and law enforcement efforts. The government and law enforcement need to work together to increase the effectiveness of rehabilitation programs for drug abusers to prevent them from becoming recidivists on a large scale.